Hemodynamics Modify Collagen Deposition in the Early Embryonic Chicken Heart Outflow Tract - Monique Y. Rennie; Stephanie Stovall; James P. Carson; Michael Danilchik; Kent L. Thornburg; Sandra Rugonyi (Journal of Cardiovascular Development and Disease, 2017)
Blood flow is critical for normal cardiac development. Hemodynamic stimuli outside of normal ranges can lead to overt cardiac defects, but how early heart tissue remodels in response to altered hemodynamics is poorly understood. This study investigated changes in tissue collagen in response to hemodynamic overload in the chicken embryonic heart outflow tract (OFT) during tubular heart stages (HH18 to HH24, ~24 h). A suture tied around the OFT at HH18 was tightened to constrict the lumen for ~24 h (constriction range at HH24: 15–60%). Expression of fibril collagens I and III and fibril organizing collagens VI and XIV were quantified at the gene and protein levels via qPCR and quantitative immunofluorescence. Collagen I was slightly elevated upstream of the band and in the cushions in banded versus control OFTs. Changes in collagen III were not observed. Collagen VI deposition was elevated downstream of the band, but not overall. Collagen XIV deposition increased throughout the OFT, and strongly correlated to lumen constriction. Interestingly, organization of collagen I fibrils was observed for the tighter banded embryos in regions that also showed increase in collagen XIV deposition, suggesting a potentially key role for collagens I and XIV in the structural adaptation of embryonic heart tissue to hemodynamic overload.